The role of feeding jejunostomy on supportive enteral nutrition for resectable esofago-gastric junction adeno carcinoma undergoing total gastrectomy and esofago jejunostomy reconstruction: a case series - Bagus, Budhi Ida (International Surgery Journal, 2023)
As a part of enhanced recovery after surgery protocols (ERAS), early gut feeding has been applicated in most of gastrointestinal surgery including major resection of distal esophageal and esofago-gastric junction adeno carcinoma. Early gut feeding could be applicated not only in minimally invasive procedure, but also in conventional open technique. Many enteral feeding option can be chosen as a post-operative enteral nutrition for the patients. One of them is feeding jejunostomy tube placement, we will evaluate the safety and effectivity of this enteral route on resectable esofago-gastric cancer resection. We will evaluate the clinical outcome of resectable esofago-gastric cancer patients and reconstruction, feeding jejunostomy tube has been placed as post-operative enteral route for nutrition. The patient with history of neoadjuvant therapy will be excluded. The post-operative evaluation including morbidity associated with jejunostomy tube will be recorded. We reported 4 cases, all of them had stage III esofago-gastric adeno carcinoma and conventional laparotomy technique was done. Feeding jejunostomy was tolerated well by the patients, enteral feeding can be started during the first 24 hours after surgery. No post-operative ileus and surgical site infection has been reported. Tube site infection was not found during this study. Although it still remains controversial, feeding jejunostomy tube was safe, feasible and has been tolerated well on esofago-gastric cancer patients undergoing resection and reconstruction.